Complex training with blood flow restriction increases power output and bar velocity during half-squat jump: a pilot randomized controlled study - Zhou, Limingfei; Tan, Yineng; Gan, Jianyu; Li, Chunlei; Bao, Dapeng; Zhou, Junhong (Frontiers in Physiology, 2024)
Purpose: This study examined the effects of 8-week complex training (CT) with blood flow restriction (BFR) on power output and bar velocity. Methods: Twenty-six healthy male university athletes (age: 19.40 ± 0.88 years) completed three sessions of CT with BFR (CT_BFRT, n=13) or CT-only (i.e., control) (n=13) per week (i.e., 24 sessions in total). Before and immediately after intervention, participants completed power measurement as assessed by one-repetition maximum (1RM) squat, squat jump (SJ), countermovement jump (CMJ), and mean power (MP), peak power (PP), mean bar velocity (Bar-MV), and peak bar velocity (Bar-PV) during the half-squat jump. Results: Two-way ANOVA models showed significant main effect of time (P < 0.001) but not group (P > 0.89) or interaction (P > 0.37) between group and time on 1RM of the squat, SJ, or CMJ; however, significant interactions were observed in MP (P = 0.03, Cohen's d = 1.39), PP (P = 0.03, Cohen's d = 1.14), Bar-MV (P = 0.04, Cohen's d = 1.26), and Bar-PV (P = 0.01, Cohen's d = 1.56). The post-hoc analyses revealed that MP, PP, Bar-MV, and Bar-PV after CT with BFRT were significantly greater compared to all the other three conditions (i.e., pre-CT_BFRT, pre-and post-CT-only). Conclusion: CT with BFR may induce significantly greater improvements in power output and bar velocity during half-squat jump and induce comparable improvements in 1RM of the squat, SJ, and CMJ of males as compared to CT only, suggesting this novel CT with BFR would be a promising strategy to enhance power performance in healthy male university athletes.